Memoirs of Mrs Inchbald, Volume 1 Including her Familiar Correspondence with the Most Distinguished Persons of her Time - Boaden, James (Cambridge library collection. British & Irish History, 17th & 18th Centuries, 1833)
Although she overcame a stammer to fulfil her acting ambitions, Elizabeth Simpson (1753–1821), known as Mrs Inchbald after her marriage in 1772, was more acclaimed for her good looks than her performances. Her husband was an actor, and she formed strong friendships with Sarah Siddons and John Philip Kemble, but her greatest impact was as a playwright, novelist, editor and critic. Despite her decision to destroy a four-volume autobiography, her extensive surviving journals and letters allowed James Boaden (1762–1839) to publish this two-volume work in 1833. Having produced biographies of Siddons, Kemble and Dorothy Jordan (which are also reissued in this series), Boaden presents here an informed account of this remarkable woman's personal, theatrical and literary life. Volume 1 covers the period from her birth to 1796 and includes as an appendix The Massacre (1792), a suppressed historical drama about the persecution of Huguenots in 1572